Penerapan Algoritma HRN pada Sistem Informasi Penjadwalan Mekanik di Ditech Injection - Sofa Marwati; Tacbir Hendro Pudjiantoro; Irma Santikarama (Prosiding SISFOTEK, 2020)
Ditech Injection Workshop is a company engaged in the maintenance of car vehicles which was established in 1998, located at Jalan Cikutra 172 and Jalan Cipedes Tengah 196 Bandung. Ditech Injection Workshop strives to improve the quality of car repair services in order to maintain competition with other workshops. There is a problem in the Ditech Injection Workshop, there are 3 to 10 consumers in 1 day who only want to be served by one mechanic, but the information on activities being carried out by the mechanic and the work time is not scheduled so the admin does not know the work being done and the estimated waiting time what is needed by consumers. Based on these problems the development of information systems is carried out by applying the HRN (Hight Ratio Next) algorithm which can help in arranging the queue service schedule. Additionally it can provide mechanical scheduling information, provide waiting time information and service priorities. The results of this study are a mechanical scheduling information system by applying an HRN algorithm that helps provide mechanical schedule information, calculate service priorities and customer waiting times